Protectionist Responses to the Crisis : Damage Observed in Product-Level Trade - McDonald, Brad (IMF Working Papers; Working Paper ;, 2011)
This paper investigates how trade flows are being affected by new discriminatory measures implemented during the global financial crisis. We match data on behind-the-border measures (e.g., bailouts and subsidies) and border measures implemented through April 2010 to monthly HS 4-digit bilateral trade data. Our estimation strategy relies on a first-differenced gravity equation and time-varying fixed effects to disentangle the impact of new discriminatory measures. Trade in exporter-importer pairs subject to new measures decreased by 5 to 8 percent relative to trade in the same product among pairs not subject to new measures. These product-level results imply global trade declines at the aggregate level of about 0.2 percent, or USD 30-35 billion a year. These aggregate figures would be higher, if one third of measures had not been excluded due to incomplete data. The paper then goes on to dissect protectionism's trade impact by disaggregating measures by type, advanced/developing countries, regions, sectors, and time. Behind-the-border measures are found to have been more harmful than border measures at the product level. Among border measures, impacts tend to be higher for less transparent measures. Advanced countries are found to be responsible for 2/3 of the trade decline due to crisis protectionism, but their exports also absorbed 2/3 of this decline. When breaking down measures in a time dimension, we find that those taken in the first nine months after the Lehman collapse were most harmful and likely continue to constitute a drag on trade.